Perturbation and noise measures in typically developing children in the age range of 6-12 years - Shaji, Arsha; Kishore, Pebbili Gopi (Journal of All India Institute of Speech and Hearing, 2013)
Perturbation and noise measures of voice have been reported to be the ones that tap subtle and early changes in voice. Although attempts have been made to document these measures in Western context, considering the geographical and ethnic variations, the same values might not be applicable in Indian context. In this context, the present study was taken up to document noise and perturbation measures in voice of typically developing children in the age range of 6-12 years and comparing them across the western norms in children and the Indian norms in adults. Participants included in the study were typically developing children with normal voice in the age range of 6-12 years. The Multi-dimensional voice profile (MDVP), advanced version (Model 5150) module with Computerized Speech Lab hardware system was used for the analysis of voice sample to obtain the perturbation measures jitter %, RAP, PPQ, sPPQ, shimmer %, APQ, sAPQ and noise measures NHR, VTI and SPI. The participants were instructed to phonate vowel /a/ at their comfortable pitch and loudness. A three second steady segment of the voice sample was used to obtain perturbation and noise measures. The obtained measures were tabulated and subjected to statistical analysis to compute mean, standard deviation and range. One way MANOVA indicated no significant effect of gender on any of the measured parameters (p>0.05). One sample t-test revealed that most of the measured parameters are significantly different from western norms in children and also from adult Indian norms. Considering these variations, it may be concluded that the database established in any population cannot be used universally and indigenous norms are essential. The results of the present study may be used as preliminary norms for children in the age range of 6-12 years.